Association between Iron-Folic Acid Supplementation during Pregnancy and Maternal and Infant Anemia in West Java, Indonesia: A Mixed-Method Prospective Cohort Study - Sartika, Ratu Ayu Dewi; Wirawan, Fadila; Putri, Primasti Nuryandari; Mohd Shukri, Nurul Husna (The American journal of tropical medicine and hygiene, 2024)
The Indonesian government has provided iron-folic acid (IFA) supplementation in response to maternal pregnancy iron-deficiency anemia. However, community-based cohorts on IFA's effects on maternal and infant anemia are limited. A mixed-method study design with a primary longitudinal cohort was used to observe the association between IFA and anemia in mothers and infants. Iron-folic acid supplementation was observed throughout pregnancy. Anemia status was based on a single hemoglobin assessment using HemoCue Hb 201 + in the second or third trimester of pregnancy for the mother and at birth for the infant. Qualitative data were collected via in-depth interviews (IDIs) and a forum group discussion (FGD). Iron-folic acid supplementation with > 180 tablets throughout pregnancy was associated with lower pregnancy anemia (adjusted relative risk [aRR] = 0.25, 95% CI: 0.092-0.664, P = 0.006) after adjusting for potential confounding variables. Supplementation with IFA was not associated with infant anemia (RR = 1.033, 95% CI: 0.70-1.54, P = 0.873 for 90-180 tablets and RR = 1.07, 95% CI 0.70-1.63, P = 0.774 for > 180 tablets). The IDIs and FGD suggested that IFA and multivitamin content knowledge, IFA consumption monitoring, and paternal involvement were important in IFA supplementation and effectiveness in reducing anemia. Iron-folic acid supplementation was associated with reduced maternal but not infant anemia. Because maternal anemia is associated with infant anemia, an anemia monitoring program for women in early pregnancy is vital in addressing infant health. Paternal involvement was also identified as a major factor in maternal and child health.